PENGARUH KOMUNIKASI TERHADAP KINERJA PEGAWAI PADA BAGIAN UMUM SEKRETARIAT DAERAH KABUPATEN KERINCI - Setiani, Eka (journal of RESIDU, 2018)
This research aim to know influence: communication to performance of worker at Bagian Umum Sekretariat Daerah Kabupaten Kerinci  Population in this research is Bagian Umum Sekretariat Daerah Kabupaten Kerinci 33 persons. Intake sampel Technique by using technique survey/sensus, whereabout individual on population as sample so sum of sampel in this research as much 33 responder. Method data collecting in this research, obtained directly with spreading quesionery. Data analyse by using instrumen tes person product moment, t test and coefficient determinasi. Result this reasearch obtained communication influence positive and significance to performance of worker at Bagian Umum Sekretariat Daerah Kabupaten Kerinci Coefficient Determinasi (Adjusted R2) equal to 0,6395 meaning is variabilitas variable dependen which can be explained by independent variabilitas variable equal to 40,90 % where Communication able to influence variable performance of worker by signifikan, while the rest equal to 59,10 %.